Genre Baru Kasidah Sufistik di Indonesia 2001-2010 - Ai Shidqi Farchah Fauziyyah; Mardani Mardani (Historia Madania: Jurnal Ilmu Sejarah, 2020)
The process of Islamization has caused acculturation among the Nusantara and foreign  culture. One of them is in the field of music, namely “Kasidah”. Initially the kasidah only used a tambourine instrument (rebana), later in its development it was mixed with Western musical instruments (guitar, bass, keyboard and drums), its name became the modern kasidah. Along with the development of the times, the Kasidah also went through a process of deculturation. Where the kasidah is no longer unique to the rebana, musicians in Indonesia have left the tambourine and only use modern musical instruments. a new genre emerged in kasidah, namely pop kasidah. This study uses historical research methods, namely research models that study past events based on the traces they have left. This research method is carried out in four stages, namely heuristics, criticism, interpretation and historiography. In 2001, a Sufi Muslim music group was born with personnel from various countries, namely Dust. They use many musical instruments from various countries as well, this is what causes the music color of Dust to be different from the others.